Career Related Foreign Language Unit Senior High - Erickson, Donna R.; Holicky, Karen R.; Minnesota State Dept. of Education, St. Paul. Pupil Personnel Services Section; Roseville Area School District 623, Minn. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1977)
Designed for use in integrating career education into the high school foreign language curriculum, this curriculum guide contains nine mini-units on the following topics: seeking employment, personnel director and job applicant, writing and typing a letter, business office worker and customers, radio producer and announcer, salesperson and shoppers, tour guide, medical worker and patient, and food tester. Each unit gives the day-by-day procedure for the teacher, the title of the activity (career or careers to be role-played), objectives, suggested student grouping, time line, list of materials needed, and the procedure to be followed in presenting student activities. These are followed by student worksheets or study materials. The guide materials are designed for French language classes, and all the student materials are in French; however the material is considered applicable to other modern languages, and the English translations are given for the convenience of other language teachers. Each unit begins with a presentation of vocabulary and with discussion relative to the career being investigated. Students are asked to make a career log in which they record new vocabulary, notes from discussions, and answers to questions. (BB)
Sponsoring Agency: Office of Career Education (DHEW/OE), Washington, DC.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Career Education; Career Exploration; Curriculum Guides; French; Fused Curriculum; High Schools; Language Experience Approach; Language Instruction; Modern Language Curriculum; Teaching Guides; Unit Plan; Units of Study; Guides, General